2012
DOI: 10.1186/1472-6882-12-93
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB p65 repression by the sesquiterpene lactone, Helenalin, contributes to the induction of autophagy cell death

Abstract: BackgroundNumerous studies have demonstrated that autophagy plays a vital role in maintaining cellular homeostasis. Interestingly, several anticancer agents were found to exert their anticancer effects by triggering autophagy. Emerging data suggest that autophagy represents a novel mechanism that can be exploited for therapeutic benefit. Pharmacologically active natural compounds such as those from marine, terrestrial plants and animals represent a promising resource for novel anticancer drugs. There are sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 37 publications
(40 reference statements)
3
39
0
Order By: Relevance
“…Arnica preparations examined in randomized double-blind human clinical trials exhibited a potent analgesic effect in patients suffering from osteoarthritis (Knuesel et al, 2002; Widrig et al, 2007). A sesquiterpene lactone isolated from Arnica flowers, helenalin, showed anti-inflammatory activity by inhibiting NFκB (Lim et al, 2012; Lyss et al, 1997), a transcription factor involved in inflammatory responses, suggesting that this constituent could be involved in Arnica’s medicinal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Arnica preparations examined in randomized double-blind human clinical trials exhibited a potent analgesic effect in patients suffering from osteoarthritis (Knuesel et al, 2002; Widrig et al, 2007). A sesquiterpene lactone isolated from Arnica flowers, helenalin, showed anti-inflammatory activity by inhibiting NFκB (Lim et al, 2012; Lyss et al, 1997), a transcription factor involved in inflammatory responses, suggesting that this constituent could be involved in Arnica’s medicinal activity.…”
Section: Resultsmentioning
confidence: 99%
“…In activated CD4+ T cells, Hln induces cell death by triggering the mitochondrial apoptotic pathway by rapid stabilization of p53, nuclear localization of p53 and AIF, and an increase in ROS production that results in loss of mitochondrial membrane potential (Berges et al 2009). In addition, it has been described that Hln mediates autophagic cell death by inhibition of NF-B p65 in other cancer cell lines, specifically in A2780 (human ovarian cancer cell line), RKO (colon carcinoma cancer cell line) and MCF-7 (breast adenocarcinoma cancer cell line) (Lim et al 2012). It has been previously shown that STLs reduce the glutathione content and increase the production of ROS in trypanosomatids (Barrera et al 2013) and that the cytotoxic effect of the STLs can be prevented by adding reducing agents like DTT or GSH (Brengio et al 2000;Jimenez-Ortiz et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…NF-κB functions to block cell death through transcriptional induction of antiapoptotic proteins and inhibits autophagy by activating mTOR [30]. Other study also demonstrated that NF-κB p65 repression contributes to the induction of autophagy [31]. Compound 1 dosedependently reduced the DNA-binding activity of NF-κB, suggesting that compound 1 has been shown to exert its effect via inhibition of NF-κB activation.…”
Section: Discussionmentioning
confidence: 96%